34 Next generation P2Y12 inhibitors improve survival in ACS: an analysis from the british cardiovascular intervention society database. (4th June 2021) - Mannan, Fahmida; Saluja, Sushant; Contractor, Hussain; Abidin, Nik; Fitchet, Alan; Tin, Lwin; Woolfson, Peter; Garg, Scot; Anderson, Simon
Abstract : Background: Dual antiplatelet therapy (DAPT) is the standard care following presentation with an acute coronary syndrome (ACS), but there remains debate regarding the relative benefits of the available P2Y12 receptor antagonists and their optimal combination with aspirin, particularly in those treated with percutaneous coronary intervention (PCI). Methods: We performed a retrospective analysis of all PCI procedures undertaken in patients with ACS recorded in the British Cardiovascular Intervention Society (BCIS) database between 2007 and 2014 who were treated with DAPT consisting of aspirin and one of either clopidogrel, prasugrel or ticagrelor. The primary outcome measure was 30-day all-cause mortality, with secondary outcome measures of mortality at 1 and 5 years. Odds ratios (OR) for mortality were determined from multivariable logistic regression models allowing for clustering by hospital. Results: Among 259, 255 eligible patients with 2 million person-years of observation, 7.4% (19, 101) of patients had ticagrelor, 7.4% (n=19, 161) had prasugrel and 85.2% (n=220, 993) were treated with clopidogrel for ACS. A total of 41, 107 (12.2%) patients died during a median of follow-up of 3.2 years (IQR: 1.6–5.2 years). Crude mortality rates were 34.7 (clopidogrel), 30.6 (prasugrel), and 36.9 deaths per 1000-person-years for ticagrelor treated ACS. In an age-sex unadjusted multinomial logistic regression analysis, mortality rates at 1 year in those treated with aspirin and ticagrelor were 64% lower [OR 0.34, 95% CI (0.32–0.36)] than those receiving DAPT with clopidogrel. DAPT with prasugrel was associated with a 27% lower mortality compared to DAPT with clopidogrel (OR 0.73 (0.69–0.77), p<0.0001). Stratifying by ACS status, the age-sex adjusted 1-year mortality rate for ticagrelor compared with clopidogrel was 63% lower [(OR 0.37 (0.34–0.40)] in STEMI and 80% lower in NSTEMI [(OR 0.20 (0.18–0.23), p<0.0001)]. The reduction in mortality at 1 year in the prasugrel versus clopidogrel group was relatively greater (57%) in individuals with STEMI [(OR 0.43 (0.40–0.45), p<0.0001)] compared to those with NSTEMI [(OR 0.64 (0.55–0.74), p<0.0001)]. Conclusions: This very large, real-world dataset of patients presenting with ACS demonstrates a significant net clinical benefit favouring the use of ticagrelor and prasugrel over clopidogrel in ACS patients for DAPT. This analysis concurs with the data from the landmark TRITON and PLATO RCTs, suggesting these agents should be considered as the standard of care in the management of ACS. Conflict of Interest: None